(untitled) (CIPEEX, 2025)
Introduction: Chagas disease remains a serious public health problem in Latin America, with a significant impact also in non-endemic countries due to migration. Among its clinical forms, Chagas megaesophagus represents a digestive manifestation of high morbidity, characterized by progressive dysphagia, regurgitation, and weight loss. In addition to the pathophysiological repercussions, these alterations significantly compromise patients’ quality of life (QOL), both physically and emotionally. Objective: To analyze the relationship between Chagas megaesophagus and the quality of life of Chagas patients in recent years, based on five original studies and systematic reviews available in national and international scientific databases. Methodology: A narrative review of the literature was conducted based on articles published between 2020 and 2025, including cross-sectional studies, systematic reviews, and clinical update articles. The descriptors used were: Chagas Disease, Chagasic Megaesophagus, Quality of Life, Achalasia, Gastrointestinal Manifestations, and Treatment. The databases consulted included SciELO, PubMed, and international open-access journals. Results: The reviewed articles showed that patients with Chagasic megaesophagus have a significant reduction in all QOL domains, assessed mainly by the SF-36, with worse performance in physical and emotional aspects. Factors such as symptom intensity (dysphagia, retrosternal pain, regurgitation), social stigma, and difficulty in accessing specialized treatment were specific as additional negative determinants. Systematic reviews also indicated that therapeutic strategies (such as dilation, Heller myotomy, and POEM) withdrawn for symptomatic improvement and consequent partial recovery of QOL. Brazilian studies highlighted the use of instruments validated in Portuguese and emphasized the need to integrate clinical and psychosocial assessment. Conclusion: Chagas’ megaesophagus significantly compromises patients’ quality of life, not only due to digestive symptoms but also due to psychosocial and functional impacts. Effective therapeutic interventions can improve QOL, but stigma and barriers to accessing healthcare remain challenges. Therefore, the need for integrated approaches that combine clinical-surgical treatment and psychosocial support to improve care for Chagas’ patients is evident.